1. \( \begin{aligned} 2 x-4 y & =-2 \\ -6 x+4 y & =-14\end{aligned} \)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Mind Expander
To solve this system of equations, we can use the substitution or elimination method. Here, we can add both equations to eliminate one variable. Adding them gives: \[ (2x - 6x) + (-4y + 4y) = -2 - 14 \] This simplifies to: \[ -4x = -16 \quad \implies \quad x = 4 \] Now substitute \( x = 4 \) back into one of the original equations, say \( 2x - 4y = -2 \): \[ 2(4) - 4y = -2 \quad \implies \quad 8 - 4y = -2 \quad \implies \quad -4y = -2 - 8 \quad \implies \quad -4y = -10 \quad \implies \quad y = \frac{10}{4} = 2.5 \] Thus, the solution is \( x = 4 \) and \( y = 2.5 \). But let's not forget to check our work! Plugging \( x = 4 \) and \( y = 2.5 \) back into the second equation, \[ -6(4) + 4(2.5) = -14 \quad \implies \quad -24 + 10 = -14 \] Since both equations hold true, our solution is verified: \( (x, y) = (4, 2.5) \).